Sustainable Energy Through Wind Speed and Power Density Analysis in Ambam, South Region of Cameroon - Kengne Signe Elie Bertrand; Kengne Signe Elie Bertrand; Kanmogne Abraham; Meva’a Lucien (Frontiers in Energy Research, 2020)
Sustainable development and the fight against climate change are now priorities in majority of countries. The contribution of renewable energies to these two ambitions has been proven. Wind being a renewable energy source, several works was carried out in this field for an effective exploitation of this resource. Thus, wind modeling using the Weibull distribution was of paramount importance. The objective of this study is to model the wind speed at Ntem, South Region of Cameroon, for good decision making on possible projects of electricity production from the wind and toward contribution to the sustainable development of rural areas in this locality. For this purpose, the average hourly wind speed data for the period of November 2012 to October 2014 provided by a station located at a height of 10 m in Ambam were used. The modeling of this wind speed by the Weibull distribution for determining the two function parameters k and C was carried out with four numerical methods: graphical method (GM), empirical method (EM), method of factor energy, and the moment method (MM). The EM presented a better performance than the other techniques. Moreover, the average density of wind energy based on the average cubic root of the cubes was estimated at 93.7628 kW/m2/year in 2013. This result presents Ambam as an unfavorable zone for wind power generation with fair wind characteristics. But it is very important to mention that, for a height of 10 m, this potential is not negligible in the Cameroonian context where domestic energy (lighting, telephone recharging, radio, television, etc.) is not yet available for most villages, located far from the national power grid.